Prevalence of Bronchial Asthma Among Secondary School Students in Dhaka City - Sarkar, S; Mumu, SJ; Mia, MS; Flora, MS; Hafez, MA (Bangladesh Medical Journal, 2014)
Asthma is a substantial health problem among children and adults worldwide, many countries having increasing prevalence of bronchial asthma. Within our knowledge no epidemiological studies have addressed the burden of bronchial asthma among secondary school students in Bangladesh. This study aimed to determine the prevalence of bronchial asthma and its associated factors among secondary school students. A cross sectional study was conducted from January 2010 to June 2010. Two hundred and fifty secondary school students from class VI to class X were randomly selected from a purposively selected secondary school at Mirpur in Dhaka city. International Studies of Asthma and Allergies in Childhood (ISAAC) core asthma questionnaire was self administered for diagnosis of asthma. Out of 250 students male was 128(51%) and female was 122(49%), mean age of the respondents was 12.9±1.2 years. Minimum education level of respondents' parents were primary, half of the respondents' father's education level was graduate and above (52.8%) and half of the respondents' mother's education level was high school (58.4%). The prevalence of bronchial asthma was 11.6% (95%CI: 7.64% to 15.56%). The proportion of bronchial asthma was higher in male than female (15.6% vs 7.4%, p<0.05). Bronchial asthma was found significantly higher among the students who had attacks of pneumonia during their childhood (under class VI) compared to children who did not (23.8% vs 9.1%, p<0.05). About 11% students were exposed to passive smoking. Passive smoking significantly associated with bronchial asthma (p<0.038). Risk indicators associated with bronchial asthma included history of pneumonia (OR=3.109, 95%CI: 1.32 to 7.29), maternal asthma (OR=2.73, 95% CI: 1.05 to 7.11) and male sex (OR=2.32, 95%CI: 1.01 to 5.33).This study showed that the prevalence of bronchial asthma was high among secondary school students than common people. Passive smoking, history of pneumonia, maternal asthma and male sex were found to be significant risk indicators for bronchial asthma. So that greater efforts are needed to prevent childhood pneumonia and passive smoking to reduce the chances of subsequent development of bronchial asthma. DOI: http://dx.doi.org/10.3329/bmj.v41i1.18778 Bangladesh Medical Journal 2012 Vol. 41 No. 1; 28-31